Padang Pariaman Regency Government Policy in Balancing Economic Interests and Environmental Sustainability: The Case of River Stone Mining in Kayutanam-Anduring - Putri, Nazhirah Luthfia; Magriasti , Lince (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines the policies of the Padang Pariaman Regency Government in balancing the economic needs of the community and environmental conservation in the case of river stone mining in the Kayutanam–Anduring area. Mining activities contribute to the economy of the community, but also cause negative impacts such as erosion, water pollution, and a decline in the quality of agricultural land. The study uses a descriptive qualitative method with Abidin's (2006) theory, which highlights four elements of policy: objectives, problems, demands, and impacts. The results of the study show that policy implementation has not been optimal due to internal constraints such as limited human resources and budget, as well as external constraints in the form of illegal mining and low environmental awareness among the community. The local government has made efforts through supervision, socialization, and the provision of alternative jobs, but these measures still need to be strengthened in order to achieve a balance between the economy and environmental sustainability.